Steroid Hormones, Immunoglobulins and Some Biochemical Parameters Changes in Patients with Breast Cancer - Yousif, Araz Muhammad; Ismail, Parween Abdulsamad; Ismail, Narmeen Abdulsamad (Diyala Journal of Medicine, 2019)
Background: Breast cancer is one of the diseases that a woman may have to face during her lifetime. Hormones play a role in breast cancer spread, determining the association between plasma hormones and breast cancer risk may provide insight into the etiology of breast cancer. Objective: To evaluate the use of sex steroid hormone levels with some biochemical parameters as a serum tumor marker in patients with breast cancer. Materials and Methods: Two groups of subjects were included, 50 patients with histologically confirmed diagnosis of Breast Cancer (group I) and 40 healthy female (group II) the age range was (35-70) years were collected from Rizgary hospital and Nanakaly hospital, in Erbil city, Iraq. During the period from May 2015 till November 2015. The measured biochemical parameters included: the level of estrogen, progesterone, prolactin, estradiol, testosterone hormones, some immunoglobulins (IgG, IgA and IgM), also ferritin, sodium and calcium ions levels have been measured in the study. Results: The results demonstrated significantly high values of steroid hormones (p<0.001, p<0.01, p<0.002, p<0.05, p<0.05 (estrogen, progesterone, prolactin, estradiol, testosterone) and significantly high values in immunoglobulins IgA, IgG, IgM in breast cancer in comparison with control group. There were also high values of sera ferritin, sodium, and calcium in women breast cancer in comparison with control group. Conclusion: An elevation of serum steroid hormone, immunoglobulins (IgA, IgG, IgM), Na, and Ca levels in cases of carcinoma breast in our study is signifies, and its importance as a marker of the disease. A serial measurement of these steroid hormones and with some biochemical parameters will have a prognostic significance and help treatment decisions.